Analysis of Head Nurse Leadership Style on Nursing Service Quality in the Intensive Care Unit at the Hospital - Romi Syahputra Tarigan; Karnirius Harefa; Tati Murni Karo Karo; Abdi Lestari Sitepu (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: Pneumonia is one of the leading causes of death in children under five in Indonesia. Pneumococcal Conjugate Vaccine (PCV) immunization is a preventive measure, yet coverage in Serdang Bedagai Regency remains low. Factors such as knowledge, education, occupation, attitude, belief, health service accessibility, and family support are suspected to influence PCV utilization. Research Objectives: This study aimed to analyze the factors influencing PCV immunization utilization at Sei Rampah Health Center, Serdang Bedagai Regency. Research Methods: This research employed an analytic survey with a cross-sectional design. The population consisted of 900 mothers with children aged 11–12 months, and a sample of 262 mothers was selected using simple random sampling. Data were collected through questionnaires and secondary data from PWS-KIA. Univariable, bivariate (Chi-square), and multivariable analyses (multiple logistic regression) were performed to identify the dominant factors. Results: Bivariate analysis indicated that education (p=0.002; OR=6.882), occupation (p=0.000; OR=6.088), and knowledge (p=0.000; OR=15.400) were significantly associated with PCV utilization. Multiple logistic regression revealed knowledge as the dominant factor (p=0.000; Exp(B)=13.063), followed by occupation, attitude, belief, and family support. Age, health service accessibility, and education did not show a significant effect. Conclusion: Parental knowledge is the key factor influencing PCV immunization utilization. Efforts to increase immunization coverage should focus on continuous education by health workers and family involvement to improve parents’ awareness and compliance with child immunization schedules.